Policy Enactment and Leader Agency - Jennifer Charteris; Dianne Smardon (New Zealand Journal of Teachers' Work)
As agents in reform processes, Principals can be pressured to respond to government and private change agendas. Far from merely implementing policy, Principals engage in complex enactments where they demonstrate agency in their interpretations and recontextualisations. Drawing data from Principal interviews, the authors consider leader agency in relation to discourses of economic rationalism, change and change leadership. The operationalisation of schooling reform and the necessity to think critically about policy within limited official consultation frameworks is highlighted. The political control of school clustering can potentially impinge on leader agency, particularly when there are additional hierarchical layers of leadership.